2019
DOI: 10.1017/s0960258519000072
|View full text |Cite
|
Sign up to set email alerts
|

Seed dormancy and longevity variability of Hirschfeldia incana L. during storage

Abstract: We studied the variability of germination, dormancy and viability loss of Hirschfeldia incana seeds in relation to seed size. Seeds were stored at 35°C under humid [75% relative humidity (RH)] or dry (33% RH) conditions. Seed germination and electrolyte leakage were evaluated periodically. Small seeds had lower longevity at humid or dry storage conditions (5 or 407 days, respectively) than large or intermediate seeds (7–9 or 536–727 days, respectively). Moreover, H. incana shows variability in seed dormancy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…This result coincides with those obtained in Jatropha curcas L. seeds, which showed a faster deterioration in AA tests over water in contrast with using a saturated salt solution [44]. Similar results were obtained with Hirschfeldia incana when comparing humid (75%) and dry (33% RH) storage at 35 °C, where humid storage decreased almost 100 times seed longevity [45]. In fact, resultant products of non-enzymatic modifications of protein structures through glycation found in accelerated aged soybean seeds were formed most rapidly in seeds at high humidity [46].…”
Section: Seed Resistance To Temperature and Relative Humiditysupporting
confidence: 88%
“…This result coincides with those obtained in Jatropha curcas L. seeds, which showed a faster deterioration in AA tests over water in contrast with using a saturated salt solution [44]. Similar results were obtained with Hirschfeldia incana when comparing humid (75%) and dry (33% RH) storage at 35 °C, where humid storage decreased almost 100 times seed longevity [45]. In fact, resultant products of non-enzymatic modifications of protein structures through glycation found in accelerated aged soybean seeds were formed most rapidly in seeds at high humidity [46].…”
Section: Seed Resistance To Temperature and Relative Humiditysupporting
confidence: 88%
“…Loss of germination potential results from accumulated ageing damage that occurs during seed storage or applied stresses. Growing evidence indicates relationships between intra-specific seed mass variation and seed deterioration associated with high temperature and relative humidity stress (Franks et al, 2019; Genna and Pérez, 2016; Guzzon et al, 2018; Mira et al, 2019). We examined water sorption characteristics of mass-separated R. mollis seeds and then evaluated responses of each mass class to various storage and stress treatments.…”
Section: Discussionmentioning
confidence: 99%
“…There is a positive exponential relationship between seed water content and seed deterioration rate for seeds held at relative humidity greater than about 30% (Ellis et al, 1990; Walters et al, 2010). Mira et al (2019) found that smaller seeds of H. incana contained more water and deteriorated more rapidly than larger seeds. However, R. mollis mass classes did not differ significantly for seed water content at higher RH, meaning that the slower deterioration observed in seeds of the heavy seed class stored in the shed should not be attributed to water content per se.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations